A hellion in her bed (New York Pocket Star Books, 2010)
Mired in scandal after his parents' mysterious deaths, notorious gambler Lord Jarret Sharpe agrees to tamely run the family brewery for a year if his Machiavellian grandmother rescinds her ultimatum that he marry. But the gambler in him can't resist w hen beguiling Annabel Lake proposes a wager. If she wins their card game, he must help save her family's foundering brewery. But if he wins, she must spend a night in his bed. The outcome sets off a chain of events that threatens to destroy all his plans.
Keywords: Gambling -- Fiction; Inheritance and succession -- Fiction; Man-woman relationships -- Fiction; Historical fiction; Love stories